Distribuição espaço-temporal do ouriço-do-mar Echinometra lucunter (LINNAEUS, 1758) (ECHINODERMATA: ECHINOIDEA) na Praia do Pacheco, Ceará. - Lima, Iracilda Ferreira da Silva. (2021)
The species Echinometra lucunter (Linnaeus, 1758) has great ecological importance, as it modifies the ecosystem's architecture and the structure of the resident community. The objective of the present work was to describe and identify its spatiotemporal distribution pattern in an intertidal area of Praia do Pacheco, Caucaia – Ceará. To analyze the spatial distribution and abundance of Echinometra lucunter, monthly samplings were carried out at low tides of syzygy (May/2019 to February/2020); three 150 m transects (T1, T2 and T3) were traced in the sandstone reefs, perpendicular to the coastline, towards the sea and equidistant 100 m. Five samples were collected from each transect, from points drawn at intervals of 30 m (0, 30, 60, 90, 120, and 150 m). The sampling area at each point was delimited with a 50 x 50 cm square, and the sea urchins found in the square were counted. The site was divided into five areas: A1 (0-30 m), A2 (31-60 m), A3 (61-90 m), A4 (91-120 m) and A5 (121-150 m), each one with five random points from each transect. For the morphometric analysis of Echinometra lucunter, 34 specimens from protected environments (tide pools) and 47 individuals from exposed areas (surf zones) were collected at low tides of syzygy (December/2020 and January/2021). The following variables were measured: total weight, weight of Aristotle's lantern and gonadal weight (in grams); height, larger diameter, carapace thickness, height of Aristotle's lantern (in centimeters). With these data, the sphericity, the Aristotle's lantern index and the gonadal index were obtained. There were 661 sea urchins in 750 squares, with 1 individual in the A1 (0 inds/m²), 59 animals in the A2 (16 inds/m²), 220 in the A3 (59 inds/m²), 181 in the A4 (49 inds/m²) and 200 specimens on the A5 (54 inds/m²). The highest densities of sea urchins occurred in the dry months (September/2019 to November/2019) and with low rainfall. The distribution pattern was aggregated, with animals occupying the areas closest to the sea. There was a significant difference between the average abundances of the five areas (p≤0.05). There were no significant variations between areas A3 and A4 and between areas A4 and A5 (p>0.05). The morphometric variables carapace thickness (cm) and gonadal index varied significantly, being higher in sea urchins collected from exposed environments (surf zones).